Sleep quality and chronotype differences in correlation to the balance control in juvenile elite speed skaters - Kulma, P. (Acta Salus Vitae, 2022)
Sleep is one of the main tools of regeneration, thanks to which physical and psychological parameters are restored and thus balances the negative impact of stress on the human body. The aim of the study is to analyze sleep quality and chronotype differences in correlation to the balance control in juvenile elite speed skaters. For the research survey it was selected 20 speed skaters (age average 17.6 years) from four elite Czech speed skating clubs. The following methods were used: content analysis, Life Rhythm and Sleep Questionnaire, University of Pittsburgh Questionnaire on Sleep Quality (PSQI), and a battery of functional balance tests. The measured data were analyzed by descriptive statistics using numerical and graphical methods, absolute and relative frequencies. The analysis of the results showed a positive correlation between the M-E score and the performance in the functional balance tests, and also showed a significant difference in the Bass test between men and women. Furthermore, it was found that men achieved a lower M-E score than women Deteriorated level of mental health was found in 10% of the examined speed skaters. The research survey thus showed that the global trend of today's society, which is a strong inclination to the evening typology, also applies to juvenile elite athletes, which is an undesirable phenomenon in terms of balance control and performance in speed skating. The results of the presented study may be useful for training focus of coaches or athletes.